Intraspecific SSR Marker Screening for Detection of Dendrobium crumenatum Mutants Generated from In Vitro Gamma Irradiation - Dwiyani, Rindang; Sanjaya, I Putu Wahyu; Yuswanti, Hestin; Darmawati, Ida Ayu Putri; Suada, I Ketut; Manullang, Prila Kartika; Fitriani, Yuyun (Journal of Tropical Biodiversity and Biotechnology, 2024)
Determination of D. crumenatum mutant obtained from in vitro mutation breeding needs a long time due to its long-life cycle. SSR molecular markers can be used for early mutant detection. Specific SSR markers developed in D. crumenatum are not yet available. Alternative published SSR markers were developed from D. catenatum. The aims of this study are to screen the most informative SSR markers generated from D. catenatum tested in irradiated D. crumenatum population and to determine the gamma irradiation dose resulting the most mutants. Ten SSR markers were randomly selected and tested in 25 individuals of D. crumenatum plantlets irradiated with several doses (0, 5, 10, 15, and 20 Gy; 5 plantlets each dose). The result showed 7 of 10 primers were polymorphic and the other three were  monomorphic. All seven polymorphic primers can be used to identified intraspecific variation in the D. crumenatum mutant population. Markers dnsr28 and dnsr98 were the most informative, with the highest polymorphic information content (PIC) value of 0.5. Irradiation D. crumenatum protocorms using 10-15 gray doses were detected as the highest mutant percentage obtained up to 100% in the sample tested. This resulting marker information can be used to screen wider mutant population to decrease the non-mutant individuals in the population for maintenance and cost efficiency. The 10-15 Gy can be used as reference doses for gamma irradiation in 3 months old D. crumenatum protocorm materials.